The Eritrean Diaspora: Savior or Gravedigger of the Regime? Diaspora Responses to the Imposition of UN Sanctions - Nicole Hirt (German Institute of Global and Area Studies (GIGA), 2013)
This article examines the impact of UN-imposed sanctions on the stability of the Eritrean regime, using diaspora behavior as an explanatory variable of crucial importance. It explores the transnational nature of Eritrean society, which is characterized by long-distance nationalism, and examines the history and structure of the Eritrean diaspora as well as its transformation since the political crisis of 2001. The paper argues that the government and its supporters among the diaspora, as well as regime opponents, have all instrumentalized the sanctions for their own specific purposes. While the former use the sanctions to create a rally around the flag effect and for fundraising purposes, the latter campaign against the 2 percent diaspora tax levied by the government because it may be used for illicit purposes in breach of the sanctions regime. However, due to the opposition's disunity and failure to organize joint campaigns, its efforts have so far failed to decisively contribute to the demise of Eritrea's crumbling rebel regime. Meanwhile financial flows to both the government's coffers and to private individuals continue to play a stabilizing role. Nevertheless, unsuccessful domestic policies, the mass exodus resulting from the militarization of the entire society and an isolationist foreign policy are all contributing to the growing weakness of the regime, and with it the State of Eritrea.
Keywords: 300; Eritrea; sanctions; transnationalism; diaspora; diaspora tax; remittances; regime change